Inferência das tecnologias nas narrativas teatrais - Pozzetti, Gislaine Regina (2017)
This work problematizes the inferences that the technologies have contributed to the theatrical constituents throughout the history culminating with the necessity of their reframing, from the digital technologies. The objective is to discuss the issues that involve the conditions of presence, creation, time, space and participation of the spectator in today's theatrical practices. For this, it is questioned, as a problem situation of this thesis, that technical, aesthetic and poetic resonances the digital technologies inferred in theatrical narratives in the 21st century. The discussion is developed with bibliographical and cartographic research as a method, which supports the guiding thread of the new arrangements, configurations, hybridizations and deterritorizations that in the human historical trajectory were organized to give feedback to theatrical practices. Case studies bring to light paradigm reconfigurations of theatrical constituencies, sacred from the Greeks, such as the spectator paradigm that contemplates, acts, and interacts; The actor paradigm that begins to act in differentiated qualities of presence; The paradigm of text dramaturgy, which begins to be constructed in co-authoring with the user; The representation space paradigm consisting of bits; The paradigm of time, in which the symmetry experienced in the action becomes uninterrupted, and finally, the paradigm for the scenic elements that, like the presence, inhabit and constitute now in physical environments, sometimes in the liquid environments, without losing Its ephemeral art feature